Features of Using Health-Saving and IC-Technologies in the Formation of a Socially Mobile Teacher in a Pandemic Condition - Nataliia M. Vinarchuk; Olha S. Haliuka; Mariia-Tereza I. Sholovii (Mukachevo State University, 2021)
The new reality caused by the coronavirus pandemic opens up the possibility of updating the content of professional training of socially mobile educators by means of health-saving and information-communication technologies. The purpose of the study is to analyse the features of the use of health and IC-technologies in the process of forming a socially mobile teacher in a pandemic. The research methodology includes theoretical analysis and generalisation of psychological and pedagogical sources, elaboration of legal documents in the field of education, study and generalisation of experience of scientific and pedagogical workers, disclosure of basic theoretical provisions, identification and substantiation of key concepts. The authors present a detailed analysis of the concepts of "health", "health-saving technologies", "information and communication technologies", "social mobility". The purpose and tasks of health-saving and IC-technologies are clarified. Ways to implement and use health-saving technologies in educational institutions during the pandemic COVID-19 have been identified. Methods of application of information and communication technologies in the conditions of distance learning are offered. A number of advantages and disadvantages of ICT in education are identified. The guidelines of successful realisation of a socially mobile teacher in the modern educational reality are determined. It has been found that social mobility as an integrative ability of an individual to adapt to the changing environment and changes dictated by society is perhaps the most important and relevant feature in our time. It is determined that the readiness to implement, combine and use in professional pedagogical activities of health-saving and IC-technologies indicates the formation of social mobility of the teacher. The experience of using health-saving and information-communication technologies by scientific and pedagogical workers of Ivan Franko National University of Lviv in the process of becoming and formation of socially mobile educators in the conditions of the COVID-19 pandemic is described. The practical value of scientific work lies in the substantiation and generalisation of pedagogical conditions for updating the content of professional training of future teachers through the prism of their ability to social mobility